Gastric denervation procedures: Round table XXVIII Uruguayan Congress of Surgery: coordinator Juan Carlos Castiglioni Barriere - Castiglioni Barriere, Juan Carlos; Balboa, Oscar; Bergalli, Luis E; Estapé, Gonzalo (Cirugía del Uruguay, 1978)
The Panel Meeting analyzed, from an exclusively technical viewpoint, the procedures far vaga! denervation of stomach, especially when referred to treatment of duodenal ulcer.